Effectiveness of Vamana karma and Shamana chikitsa in Vicharchika Kusta (Allergic Contact Dermatitis) - A Case Study - Prashanth Bhat; Manjunath S. Udikeri (Indian Journal of Ayurveda and Integrative Medicine KLEU)
Skin disorders are prevalent health issues that can lead to significant physical discomfort and psychological distress. In Ayurveda, Kushta encompasses a broad spectrum of skin diseases, characterized by the involvement of multiple body tissues and doshas. This case report discusses the Ayurvedic approach in managing a chronic case of Kushta. A patient presented with chronic skin lesions consistent with Kushta, experiencing symptoms such as discoloration and discomfort. The condition had persisted despite previous treatments, significantly affecting the patient’s quality of life. The patient underwent a comprehensive Ayurvedic treatment regimen, including both Shamana (palliative) and Shodhana (purificatory) therapies. Over the course of treatment, significant improvements were observed in skin appearance and symptom relief, with no reported adverse effects. This case highlights the potential effectiveness of traditional Ayurvedic interventions in managing chronic skin conditions like Kushta. Further studies may explore the integration of such approaches into broader dermatological practice.